Linguistic dualities: Deconstructible or defensible? - van Rooy, Bertus (Stellenbosch Papers in Linguistics Plus, 2023)
At least since Saussure, the idea that language can be understood through a number of dualities has been a defining trope of linguistic theorising. In this squib I propose that a better appreciation of the kinds of binary pairs, together with a richer notion of the functions of language and the possibility of simultaneity rather than complementarity in at least some of the concept pairs, may yet serve to rescue some pairs of concepts and provide fruitful, if forever provisional, understanding of linguistics as a discipline and language as an object of investigation.